The Urgency of Multicultural Education in the Formation of Student Character - Hesty Evang Gelista Silalahi (LPPM Institut Studi Islam Sunan Doe, 2022)
Multicultural education is an approach process in transferring the values of diversity which are the identity of the Indonesian people through teaching, in order to create an attitude of social tolerance in students. The values in multicultural education include self-identity, diversity, equality, tolerance and empathy. Multicultural education can be used as a defense against diversity conflicts in Indonesian society. This study aims to see how important multicultural education is placed in educational institutions as an effort to build the character of students. The research method focuses on efforts to describe the object under study by gathering information that is relevant and related to the core issues discussed through literature study. The results of this study are regarding the background of the emergence of multicultural education in several countries, the process of internalizing multicultural education carried out by educators in learning which includes strategies, models and principles used in implementing multicultural education to students and the importance of implementing multicultural education to be carried out in Indonesia.